HUBUNGAN MEKANISME KOPING INDIVIDU DENGAN KECEMASAN KOMUNIKASI INTERPERSONAL PADA MAHASISWA NERS - Eko Mulyadi; Syaifurrahman Hidayat (Wiraraja Medika : Jurnal Kesehatan, 2014)
Anxietyis anindividual response toasituationthat isnotfunandexperienced byallliving thingsineveryday life. One of the causesofanxietyin communicationislack of confidence. Effective copingproducepersistentadaptationisa newandimprovedhabitsof theold situation, whileineffectivecopingendedwithmaladaptivebehaviorisbehavior that deviatesfromnormativedesiresandmayharm themselvesor othersorobjective environmentin this studyistodetermine the relationship ofthe individualwithanxietycoping mechanismsof interpersonal communicationin StudentnursesThis research is a descriptive analytic study using cross-sectional approach. The population in this study was all students of nurses professional study program Health Faculty Wiraraja University Sumenep 2013/2014 academic year, amounting to 77 students. The Total sampling was using sampling. Technical analysis of the data in this study using the Chi-square formula with a significant level (p) = a = 0.05 or 5%.The results ofthe studyarethe respondentshavepartiallyadaptivecoping mechanismsandmost respondentshad anxietyinterpersonalcommunicationwithmildanxietycategory, withconclusionsThere is a relationshipwith theindividual copingmechanismsanxietyinterpersonal communicationin StudentNursesHealth Faculty WirarajaSumenep.